The Influence of Animated Video Media on Students' Learning Interest in Islamic Religious Education Learning - Winda Irsyidah Kholish Siregar; Tomi Satria; Prima Aswirna (EDUJAVARE: International Journal of Educational Research, 2026)
Islamic Religious Education learning needs to be supported by the use of media that can attract students' attention and suit their learning needs. One of the media that can be utilized is animated video because it is able to present material more interestingly through a combination of images, sound, text, and animation. This study aims to determine the effect of using animated video media on students' learning interest in Islamic Religious Education subjects at SD Negeri 100202 Napa. This study uses a quantitative approach with an experimental method and a Pre-Experimental Design type One Group Pretest-Posttest Design. The research sample consisted of 30 sixth grade students. The research data were obtained through a learning interest questionnaire given before and after the use of animated video media. The collected data were analyzed using descriptive and inferential statistics, including the Liliefors normality test and the paired sample t-test at a significance level of 0.05. The results showed that the average student learning interest increased from 88.00 in the pretest to 94.73 in the posttest with a difference of 6.73 points. The hypothesis test results obtained a significance value of 0.000 (<0.05), indicating that animated video media significantly influenced students' learning interest. Therefore, animated video media can be used as an effective alternative learning medium to increase student interest in Islamic Religious Education (ISE) in elementary schools.